P14.85 Impact of the neuro-radiologist and neuro-surgeon in contouring with the neuro-oncologist on local relapse rates for brain metastases treated with stereotactic radiosurgery. (9th September 2021) - Robinson, M; Sayal, K; Tunstall, C; Padmanaban, S; Watson, R; Pretorius, P; Joseph, R; Jeyaretna, S; Hobbs, C
Abstract: BACKGROUND: The audit evaluates the value of MDT, including neuro-radiologist and neuro-surgeon, review of contouring carried out by a clinical oncologist in stereotactic radiosurgery (SRS). MATERIAL AND METHODS: A sequential audit was conducted of all patients receiving intracranial SRS at our local institution for the first 22 months of a new SRS service. Lesions were contoured first by clinical oncologist then reviewed/edited by the MDT. The initial contour was compared with final contour using Jaccard conformity and geographical miss indices. The dosimetric impact of a contouring change was assessed using plan metrics to both original and final contour. The impact of the contouring review on local relapse, overall survival and radio necrosis rate was evaluated with at least 24 months follow up (24–46 months). RESULTS: 113 patients and 142 lesions treated over 22 months were identified. Mean JCI was 0.92 (0.32–1.00) and 38% needed significant editing (JCI<0.95). Mean GMI was 0.03 (0.0–0.65) and 17% showed significant miss (GMI>0.05). Resection cavities showed more changes, with lower JCI and higher GMI (p<0.05). There was no significant improvement on JCI or GMI shown over time. Dosimetric analysis indicated a strong association of conformity metrics with PTV dose metrics; a 0.1 change in GTV conformity metric association with 6–17% change in dose to 95% of resulting PTV. Greater association was seen in resection cavity suggesting the geographical nature of a typical contouring error gives rise to greater potential change in dose. Clinical outcomes compared well with published series. Median survival was 20 months and local relapse free rate in the treated areas of 0.89 (0.8–0.94) at 40 months, and 0.9 (0.83–0.95) radio-necrosis free rate at 40 months with a median 17 months to developing radio-necrosis for those that did. CONCLUSION: This work highlights that a MDT contour review adds significant value to SRS and the approach translates into reduced local recurrence rates at our local institution compared with previously published data. Radio-necrosis rates are below 10%. No improvement in clinical oncologist contouring over time was shown indicating a collaborative approach is needed regardless of experience of clinical oncologist. MDT input is recommended in particular in contouring of resection cavities.